Development of return to work management model - อันติมานนท์ อรพันธ์; สายแปง ธิติรัตน์; ศิริรัตนพฤกษ์ สมเกียรติ; บุญมีพงศ์ โกวิทย์; พรหมรัตน์ อารีพิศ; สุขอนันต์ กมลชนก (Disease Control Journal, 2018)
This participatory action research aimed to develop the return to work management model linking between health care providers and workplaces. The study was conducted during July 2015- August 2016 in 8 hospitals and it was divided into three phases including Phase I: situation analysis of return to work interventions done by health care providers; Phase II: tool and RTW management model development; and Phase III: conclusions. Results showed that in the past most physicians had only given a doctor certificate to the sick/injured factory employees who were absent from work but had not worked with the workplaces on the recommendations or decisions regarding potential change of job title or working conditions of the returning employees, while on the part of health facilities a hospital executive committee had made the decision regarding the change of job title among sick/injured health workers. RTW interventions were implemented in three of eight hospitals with different figures and there was insufficient involvement of the workplaces. Six RTW forms including RTW01-RTW06 were developed by the staff of participating hospitals and workplaces, tried out in eight hospitals, and revised and refined until they were found suitable for actual work environments. The model of RTW management was also developed and it was comprised of two parts. The first part specifically addressed a hospital-based RTW intervention and the second part was intended to focus on a workplace-based RTW intervention. The key components of RTW management model included the criteria for patient inclusion into the program, the communications between occupational physicians and treating physicians, the coordination between health care providers and the workplaces, and the provision of modified work/position descriptions for sick or injured workers. Modified work/position descriptions is defined as either a modification of the original job to reduce physical loads, reduced hours or the transfer of the recovering worker to a less demanding job. Among eight participating hospitals, all of them could successfully perform RTW interventions according to the RTW forms and model provision. These hospitals, however, modified the model to suit their actual work settings. Finally, the roles of workplace to implement RTW interventions were quantified. The number of patients included in the RTW program has increased as well. Staff of participating hospitals and workplaces were found to have actively contributed to all phases of the study, including idea formulation, RTW form and model development and implementation. It is recommended that private hospitals be considered for inclusion and participation in the model for future development because most workers insured under the Social Security Scheme (SSS) choose private hospitals to access health services. Additionally, related agencies under the Ministry of Labour should support the workplaces to implement the RTW program in compliance with the applicable laws, as well as working closely together with health care providers.